THE PROFESSIONAL DEVELOPMENT OF PHYSICIAN: THE CHOICE OF STRATEGIES AND THE SPECIFIC PROCESS OF PROFESSIONALIZATION - R. V. Shurupova (Сеченовский вестник)
The article under review is about the professional development of physician, special attention is paid to the process of self-perfection of physician-teachers.